Microwave synthesis and mechanistic examination of the transition metal carbides - Vallance, Simon (2009)
This thesis aims to describe the ultra-rapid synthesis of a number of important transition metal carbides as well as investigating their reaction mechanisms. 4 binary systems are discussed; Nb-C, Mo-C, Ta-C and W-C, and work carried out on the ternary system, Nb-Ta-C, is also evaluated. Carbide production was investigated from both the oxide and elemental precursors.